Willingness to Vaccinate Against Herpes Zoster and Its Associated Factors Across WHO Regions: Global Systematic Review and Meta-Analysis - Qiang Wang; Liuqing Yang; Lan Li; Chang Liu; Hui Jin; Leesa Lin (JMIR Publications, 2023)
BackgroundA life-course immunization approach would enhance the quality of life across all age groups and improve societal well-being. The herpes zoster (HZ) vaccine is highly recommended for older adults to prevent HZ infection and related complications. The proportions of willingness to receive the HZ vaccine varies across countries, and various kinds of factors, including sociodemographics and individual perceptions, influence the willingness to vaccinate. ObjectiveWe aim to estimate the HZ vaccination willingness rate and identify factors associated with vaccine uptake willingness across all World Health Organization (WHO) regions. MethodsA global systematic search was performed on PubMed, Web of Science, and the Cochrane Library for all papers related to the HZ vaccine published until June 20, 2022. Study characteristics were extracted for each included study. Using double arcsine transformation, vaccination willingness rates with 95% CIs were pooled and reported. The willingness rate and associated factors were analyzed by geographical context. Associated factors were also summarized based on Health Belief Model (HBM) constructs. ResultsOf the 26,942 identified records, 13 (0.05%) papers were included, covering 14,066 individuals from 8 countries in 4 WHO regions (Eastern Mediterranean Region, European Region, Region of the Americas, and Western Pacific Region). The pooled vaccination willingness rate was 55.74% (95% CI 40.85%-70.13%). Of adults aged ≥50 years, 56.06% were willing to receive the HZ vaccine. After receiving health care workers' (HCWs) recommendations, 75.19% of individuals were willing to get the HZ vaccine; without HCWs' recommendations, the willingness rate was only 49.39%. The willingness rate was more than 70% in the Eastern Mediterranean Region and approximately 55% in the Western Pacific Region. The willingness rate was the highest in the United Arab Emirates and the lowest in China and the United Kingdom. The perception of HZ severity and susceptibility was positively associated with vaccination willingness. The perceived barriers to vaccination willingness (main reasons for unwillingness) included low trust in the effectiveness of the HZ vaccine, concerns about safety, financial concerns, and being unaware of the HZ vaccine's availability. Older individuals, those having lower education, or those having lower income levels were less likely to willing to be vaccinated. ConclusionsOnly 1 in 2 individuals showed a willingness to be vaccinated against HZ. The willingness rate was the highest in the Eastern Mediterranean Region. Our findings show the critical role HCWs play in promoting HZ vaccination. Monitoring HZ vaccination willingness is necessary to inform public health decision-making. These findings provide critical insights for designing future life-course immunization programs.